A taxonomic and ecological study of the living and fossil hystricidae with particular reference to Southern Africa. - Maguire, J. M. (My University, 1976)
The taxonomy of modern and fossil Hystricidae and the evolutionary history of the family has been reviewed, with particular reference to 203 undescribed South African specimens from the Transvaal australopithecine deposits and Cave of Hearths. After comparison with all contemporaneous fossil forms (only 10 of the 28 described fossil species seem valid) it was concluded that Xenohystrix crassidens Greenwood 1955, Hystrix makapanensis (Greenwood 1958) and H. africaeaustralis Peters 1852 are present at Hakapansgat Limeworks, whereas only the latter species is present at the remaining australopithecine sites, with the possible exception of a few tentatively referred specimens of H. makapanensis. There are insufficient grounds for erecting a distinct species for the fossil form of H. africaeaustralis present in the australopithecine deposits and the Cave of Hearths material is likewise referred to the modern species. The distribution and minimum numbers of individuals of porcupine species present in the different breccias of the five sites is detailed and a reconstruction of the skull and mandible of X. crassidens attempted. The environment, stratigraphy and potential ages of the source deposits is discussed; it is concluded that with the exception of Taung, the dates suggested by Partridge and Vrba agree with the limited evidence provided by the fossil Hystricidae. Numerous skull characters used in the diagnoses of new Hystrix were examined for variability within a single modern species (only 3 of the 77 extant species proved to be valid) and then tested for diagnostic significance by comparison with the remaining valid species. Special attention was paid to mandibular and dental characters, particularly the crown enamel pattern, but the only reliable diagnostic characters were found to be associated with the anterior part of the cranium, which is seldom preserved in fossil form. The sequence of tooth replacement, a method for identifying isolated teeth, methods for segregating specimens into growth stages, and a standard terminology have been outlined. A taphonomic study, attempting to determine the extent to which fossil porcupines may have been responsible for the accumulation of the Makapansgat Limeworks bone assemblage and for the manufacture of the bone tools described by Dart, was undertaken. Unlike the fossil assemblage porcupine bone accumulations are characterized by a high percentage of much-gnawed bones, a large average fragment size, a high proportion of intact shafts with the concomitant near-absence of bone flakes anci a low survival potential for the articular ends of all limb bones. Comparison showed that the damage done by porcupines differs from that evident on the corresponding skeletal elements from Makapansgat. It is concluded that fossil porcupines had very little to do with either the accumulation or fracture of the Makapansgat Limeworks bones.
Thesis submitted to the Faculty of Science at the University of the Witwatersrand, Johannesburg in fulfillment of the requirements for the Degree of Doctor of Philosophy.
Keywords: Porcupines.; Porcupines, Fossil -- Africa, Southern.; Mammals, Fossil -- Africa, Southern.